Pengaruh Penerapan Sistem Keuangan Desa (SISKEUDES) dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan (Studi Kasus Pada Desa Nita dan Desa Lusitada) - Petrus M. Pedro Wisang; Wilhelmina Mitan; Wihelmina M. Yulia Jaeng (Universitas 45 Surabaya, 2023)
This study aims to examine the effect of the implementation of the Village Financial System and Human Resource Competence on the Quality of Village Financial Reports case studies at the offices of Nita Village and Lusitada Village, Sikka Regency. The data source in this study was primary data using data collection techniques using questionnaires distributed to 32 respondents at the Nita Village Office and the Lusitada Village Office. The data analysis method used in this study is regression analysis. The results of the study show that the implementation of the Village Financial System does not affect the quality of financial reports, while the Competence of Human Resources influences the quality of Village financial reports.